The Suffix Tree of a Tree and Minimizing Sequential Transducers - Breslauer, Dany (BRICS Report Series, 1995)
This paper gives a linear-time algorithm for the construction of the suffix tree of a tree. The suffix tree of a tree is used to obtain an efficient algorithm for the minimization of sequential transducers.